Chitosan-Based Drug Delivery Systems for Optimization of Photodynamic Therapy: a Review - Calixto, Giovana Maria Fioramonti [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Victorelli, Francesca Damiani [UNESP]; Frade, Maria Lucia [UNESP]; Ferreira, Paula Scanavez [UNESP]; Chorilli, Marlus [UNESP]; Fontana, Carla Raquel [UNESP] (Springer Nature, 2019)
Drug delivery systems (DDS) can be designed to enrich the pharmacological and therapeutic properties of several drugs. Many of the initial obstacles that impeded the clinical applications of conventional DDS have been overcome with nanotechnology-based DDS, especially those formed by chitosan (CS). CS is a linear polysaccharide obtained by the deacetylation of chitin, which has potential properties such as biocompatibility, hydrophilicity, biodegradability, non-toxicity, high bioavailability, simplicity of modification, aqueous solubility, and excellent chemical resistance. Furthermore, CS can prepare several DDS as films, gels, nanoparticles, and microparticles to improve delivery of drugs, such as photosensitizers (PS). Thus, CS-based DDS are broadly investigated for photodynamic therapy (PDT) of cancer and fungal and bacterial diseases. In PDT, a PS is activated by light of a specific wavelength, which provokes selective damage to the target tissue and its surrounding vasculature, but most PS have low water solubility and cutaneous photosensitivity impairing the clinical use of PDT. Based on this, the application of nanotechnology using chitosan-based DDS in PDT may offer great possibilities in the treatment of diseases. Therefore, this review presents numerous applications of chitosan-based DDS in order to improve the PDT for cancer and fungal and bacterial diseases.
Keywords: Chitosan; Drug delivery systems; Nanotechnology; Photodynamic therapy